STUDY OF PARAMETERS INFLUENCING BIOSYNTHESIS PROCESS OF GOLD NANOPARTICLES USING PLANT EXTRACTS AS REDUCING AGENTS: A COMPREHENSIVE REVIEW - Yusril Haidar Hamdani, Muhammad
Gold nanoparticles become an important material in the application in the field of health and industry. Gold nanoparticles are often applied in medical concerns, such as drug delivery agents and X-ray imaging. Moreover, gold nanoparticles can be used in the manufacture of biosensors and catalysts. Synthesis of gold nanoparticles is generally carried out through physical and chemical processes. However, those kind of processes utilize a dangerous substance which is not environmentally friendly and require expensive manufacturing costs. Thus, synthesis through biological processes is being developed to overcome these problems. One of the reducing agents that can be used is plant extracts that contain a variety of biomolecular substances. There still a few researches that focused on the effect of the biosynthetic process parameters, therefore this comprehensive review can be used as an initial consideration in the development of biosynthesis of gold nanoparticles. Before the main review, research source collection was carried out to provide initial general information about nanoparticles, gold nanoparticles, and the biosynthesis process of gold nanoparticles. After that, a several research sources will be compared and analyzed to make some conclusion about effect of parameters. Parameters that will be discussed in this study are HAuCl4 concentration, extract volume, pH, and temperature. UV-Visible Absorption Spectroscopy and Transmission Electron Microscope (TEM) images were analyzed in each experimental condition. The comprehensive review shows that variations in parameters cause differences in the size and shape of the formed gold nanoparticles. From various research sources, it can be concluded that the optimum conditions of each parameter are: 1 mM HAuCl4, 5% (v/v) volume of extract, pH 6, and at 80°C . In addition, the shape of spherical particles tends to form when the reaction rate is fast and the number of biomolecular substances are sufficient so the reduction and stabilization processes take place optimally. When the particles are well stabilized, the growth process of the particles can be avoided. Growth process can produce particles with triangular and hexagonal shapes.